Effect of combining steel fibers with crumb rubber on enhancing the behavior of beam-column joints under cyclic loading. (1st March 2019) - AbdelAleem, Basem H.; Hassan, Assem A.A.
Highlights: Structural performance of beam-column joints under cyclic loading is investigated. Adding CR up to optimum level enhanced the joint ductility and energy dissipation. Increasing the CR percentage above optimum level changed the failure mode. Combining SFs with CR significantly improved the behavior of beam-column joints. Using a larger coarse aggregate helped to improve the shear capacity of the joint. Abstract: This investigation aims to study the structural performance of beam-column joints under reverse cyclic loading. Different self-consolidating concrete (SCC) mixtures with various percentages of crumb rubber (CR) and steel fibers (SFs) were tested. The effect of combining different lengths and volumes of SFs with CR on enhancing the ductile behavior of the tested joints was investigated. The main parameters were the percentage of CR (0%-25% by volume of sand), coarse aggregate size (10 mm and 20 mm), concrete type (SCC and vibrated concrete), length of SFs (35 mm and 60 mm), and volume of SFs (0%, 0.35%, and 1%). The structural performance of the tested beam-column joints was evaluated based on load carrying capacity, load deflection response, initial stiffness, rate of stiffness degradation, failure mode, cracking behavior, displacement ductility, brittleness index, and energy dissipation. The results indicated that combining SFs with CR significantly improved the deformability, ductility, energy dissipation, initial stiffness, cracking behavior, first crack load, and load carrying capacity of beam-column joints under reverse cyclic loading. The results also showed that at high percentage of CR (20%), using a larger coarse aggregate (20 mm compared to 10 mm) helped to improve the shear capacity of the joint and changed the failure mode from BJ-mode to B-mode, which enhanced the load carrying capacity, ductility, and energy dissipation of the tested joint.